Superior tensile properties of 1%C-CoCrFeMnNi high-entropy alloy additively manufactured by selective laser melting. Issue 1 (2nd January 2020) - Park, Jeong Min; Choe, Jungho; Kim, Jung Gi; Bae, Jae Wung; Moon, Jongun; Yang, Sangsun; Kim, Kyung Tae; Yu, Ji-Hun; Kim, Hyoung Seop
Abstract : CoCrFeMnNi high-entropy alloys containing 1 at% carbon (C-HEAs) were additively manufactured using selective laser melting (SLM). Superior tensile properties of the as-built C-HEA (to previously reported ones) were achieved by utilizing multiple strengthening mechanisms (i.e. solid solution, grain refinement, dislocation density, and nano-precipitation) by this new manufacturing method. In particular, the SLM process could allow to maximize the strengthening effect of carbon addition to HEAs via finely distributed nano-carbides at the boundaries of solidification cellular structure.  This work will open a new window to utilize the SLM process for enhanced mechanical properties of HEAs with great potential. GRAPHICAL ABSTRACT: IMPACT STATEMENT: CoCrFeMnNi high-entropy alloys containing 1 at% carbon were successfully produced by selective laser melting, and the alloys exhibited much better tensile performance than additive manufactured high-entropy alloy previously reported.